2020
DOI: 10.1038/s41598-020-63164-8
|View full text |Cite
|
Sign up to set email alerts
|

Inter-patient variations in relative biological effectiveness for cranio-spinal irradiation with protons

Abstract: cranio-spinal irradiation (cSi) using protons has dosimetric advantages compared to photons and isexpected to reduce risk of adverse effects. The proton relative biological effectiveness (RBE) varies with linear energy transfer (LET), tissue type and dose, but a variable RBE has not replaced the constant RBE of 1.1 in clinical treatment planning. We examined inter-patient variations in RBE for ten proton CSI patients. Variable RBE models were used to obtain RBE and RBE-weighted doses. RBE was quantified in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Dose/volume parameters associated with white matter damage (%V40Gy) and reduction of neural stem cell number (%V10Gy) were analyzed with respect to the variable RBE models for all BSCs [33]. Discrete RBE mean dose values (RBE d ) for each structure were reported by dividing the RBEweighted mean dose from each model by the physical mean dose (RBE ¼ 1.0) (further details in [34]). Associated decline The second column shows which models are included in each category.…”
Section: Dose/volume and Rbe Analysismentioning
confidence: 99%
“…Dose/volume parameters associated with white matter damage (%V40Gy) and reduction of neural stem cell number (%V10Gy) were analyzed with respect to the variable RBE models for all BSCs [33]. Discrete RBE mean dose values (RBE d ) for each structure were reported by dividing the RBEweighted mean dose from each model by the physical mean dose (RBE ¼ 1.0) (further details in [34]). Associated decline The second column shows which models are included in each category.…”
Section: Dose/volume and Rbe Analysismentioning
confidence: 99%
“…In addition, the impact of the variable RBE on secondary cancer risk was not considered in the current model. Consequently, generalizing the results of this study www.nature.com/scientificreports/ may be challenging due to inherent biological uncertainties, model limitations in accounting for RBE in tumor initiation, and the presence of significant inter-patient variation 68,69 . Nevertheless, these findings are expected to provide valuable insights for clinicians and patients in their decision-making processes, particularly in the context of reducing the secondary cancer risk when considering PBT.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been carried out to evaluate the dosimetric effects of different RBE models in passive scattering proton therapy [ 80 ], and IMPT plans for numerous tumor sites including H&N [ 81 85 ], thorax [ 84 , 86 ], liver [ 81 ], prostate [ 84 , 87 , 88 ], and craniospinal irradiations [ 89 ]. Tilly et al [ 68 ] first reported the influence on the dose volume histograms after RBE correction for a patient with hypopharynx cancer.…”
Section: Use Of Let In Handn Plan Evaluation and Patient Outcome Studymentioning
confidence: 99%